Pelatihan Operasional Sistem Kasir Digital bagi Pelaku UMKM di Desa Ulapato A - Asral Kelvin s.r Saharai (Madani: Jurnal Pengabdian Ilmiah, 2026)
The development of digital technology has encouraged micro, small, and medium enterprises (MSMEs) to adapt more modern business management systems. However, a significant number of MSME operators in Ulapato.a Village still rely on manual transaction recording, which leads to bookkeeping errors, difficulties in stock control, and delays in preparing financial reports. This community service activity aimed to improve the ability of MSME operators to use digital cash register systems (Point of Sale/POS) so that business transactions become more effective, efficient, and well-documented. The methods used in this activity included observation, needs identification, material delivery, hands-on practice with digital cashier applications, mentoring, and evaluation. Participants consisted of MSME operators engaged in trade, culinary, and services sectors in Ulapato.a Village. The results showed that participants were able to understand the functions of the digital cashier system, input product data, record sales transactions, manage inventory, and generate daily sales reports. This training had a positive impact on improving digital literacy and business management efficiency among MSME operators in Ulapato.a Village.